2021
DOI: 10.1155/2021/6697900
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the PEΔIII-LC3-KDEL3 Chimeric Protein of Entamoeba histolytica-Lectin as a Vaccine Candidate against Amebic Liver Abscess

Abstract: Entamoeba histolytica is an intestinal parasite that causes dysentery and amebic liver abscess. E. histolytica has the capability to invade host tissue by union of virulence factor Gal/GalNAc lectin; this molecule induces an adherence-inhibitory antibody response as well as to protect against amebic liver abscess (ALA). The present work showed the effect of the immunization with PEΔIII-LC3-KDEL3 recombinant protein. In vitro, this candidate vaccine inhibited adherence of E. histolytica trophozoites to HepG2 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…These results demonstrated that PEDV S-B group could induce Th1-dominant cellular immune responses. Our results were consistent with previous studies, which showed that PE(ΔIII) delivering antigen proteins improved cellular immune responses in vivo (Yang et al 2013;Martínez et al 2021).…”
supporting
confidence: 93%
“…These results demonstrated that PEDV S-B group could induce Th1-dominant cellular immune responses. Our results were consistent with previous studies, which showed that PE(ΔIII) delivering antigen proteins improved cellular immune responses in vivo (Yang et al 2013;Martínez et al 2021).…”
supporting
confidence: 93%
“…Regarding its molecular mechanism, E. histolytica uses the virulence factor Gal/GalNAc lectin in order to invade the host tissue; this molecule not only protects against ALAs but also induces an adherence-inhibitory antibody response[ 3 ]. In addition, E. histolytica has a pair of low-molecular-weight protein tyrosine phosphatase (LMW-PTP) genes, EhLMW-PTP1 and EhLMW-PTP2 , which are expressed through cysts, cultured trophozoites, and clinical isolates[ 32 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Immunization using a chimeric vaccine (using the recombinant protein PEΔIII-LC3-KDEL3) was successful in preventing invasive amebiasis, avoiding acute proinflammatory response, and rapidly activating a protective response. Ultimately, this recombinant protein induced increased serum levels of IgG[ 3 ]. Additionally, in order to proactively eliminate the disease, it would be beneficial to have greater awareness among at-risk members of the public[ 8 ].…”
Section: Preventionmentioning
confidence: 99%
“…In a study conducted by Martinez-Hernandez et al (2017; 2021) [34,35], the newly developed recombinant chimeric vaccine (PE∆III-LC3-KDEL3) produced from the LC3 fragment of E. histolytica, domains I and II of Pseudomonas aeruginosa, and the carboxy-terminal signal KDEL3 in Pichia pastoris has potential as an immunogen and showed the inhibition of the adherence of trophozoites to the HepG2 cell monolayer in a hamster model. Furthermore, the vaccine protects against liver tissue damage and uncontrolled inflammation.…”
Section: Gal/galnac Lectinmentioning
confidence: 99%